2021
DOI: 10.1016/j.jcv.2021.104820
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the rapid high-throughput automated electrochemiluminescence immunoassay targeting total antibodies to the SARS-CoV-2 spike protein receptor binding domain in comparison to the neutralization assay

Abstract: Background Neutralization tests (NT) are the gold standard for detecting and quantifying anti-SARS-CoV-2 neutralizing antibodies (NAb), but their complexity restricts them to research settings or reference laboratories. Antibodies against S protein receptor binding domain (RBD) have been shown to confer a neutralizing activity against SARS-CoV-2. Assays quantitatively measuring anti-S1-RBD-SARS-CoV-2 antibodies could be of great value for NAb screening of potential donors for convalescent-phase pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 20 publications
3
69
2
Order By: Relevance
“…Second, neutralizing activity was not measured. However, the assay we employed has been shown closely correlated with the titer of neutralizing antibody [ 17 ], and 99.5% of our study subjects achieved a serum antibody level above the cut-off of 133 U/mL to predict a neutralizing activity. Third, we only assessed the antibody responses and did not assess the cellular ones.…”
Section: Discussionmentioning
confidence: 99%
“…Second, neutralizing activity was not measured. However, the assay we employed has been shown closely correlated with the titer of neutralizing antibody [ 17 ], and 99.5% of our study subjects achieved a serum antibody level above the cut-off of 133 U/mL to predict a neutralizing activity. Third, we only assessed the antibody responses and did not assess the cellular ones.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with titers above 250 U/ml were manually diluted 1:100 in dilution buffer according to the manufacturer's recommendations to increase the linear range to 25000 U/ml. A mathematical transposition of Elecsys anti-S1-RBD-SARS-CoV-2 specific U/ml to the World Health Organization (WHO) standard BAU/ml was performed using the following equation: U/ml = 0.972 x BAU/ml ( Resman Rus et al, 2021 ). Since it has been previously demonstrated that an anti-S1-RBD-SARS-CoV-2 antibody concentration of more than 133 BAU/ml predicts the presence of neutralizing antibodies after natural infection ( Resman Rus et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…A mathematical transposition of Elecsys anti-S1-RBD-SARS-CoV-2 specific U/ml to the World Health Organization (WHO) standard BAU/ml was performed using the following equation: U/ml = 0.972 x BAU/ml ( Resman Rus et al, 2021 ). Since it has been previously demonstrated that an anti-S1-RBD-SARS-CoV-2 antibody concentration of more than 133 BAU/ml predicts the presence of neutralizing antibodies after natural infection ( Resman Rus et al, 2021 ). It may thus be a potential surrogate for high protection from COVID-19 after vaccination, we specifically calculated the percentage of different subgroups of our study cohort with antibody titers above this threshold.…”
Section: Methodsmentioning
confidence: 99%
“…For the total antibody assay, alternative cut-offs (i.e. 15 U/mL and 133 U/mL) 21,22 were also investigated.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…For the total antibody assay, a mean time of 830 days (95% CI: 508 -1,000) in seronegatives and 718 days (95% CI: 425 -826) in seropositives would be needed to cross the threshold of 15 U/mL which was de ned by the manufacturer as a cut-off for detection of inhibitory effects. 21 Using the threshold of 133 U/mL, 22 the mean time needed would be 470 days (95% CI: 341 -585) and 507 days (95% CI: 359 -591) in seronegative and seropositive subjects, respectively. Among the 1,443 samples analyzed on both assays, IgG and total anti-S antibodies showed an almost perfect agreement (i.e.…”
Section: Igg and Total Antibodiesmentioning
confidence: 99%